2005
DOI: 10.1021/jp044807f
|View full text |Cite
|
Sign up to set email alerts
|

Supercooled Water in PVA Matrixes. II. A Molecular Dynamics Simulation Study and Comparison with QENS Results

Abstract: Molecular dynamics (MD) simulations were carried out to elucidate the dynamic behavior of water confined in poly(vinyl alcohol), PVA, hydrogels. Model topology is supported by experimental network parameters, and simulation results are compared to an incoherent quasielastic neutron scattering (QENS) investigation carried out on PVA hydrogels.1 From the QENS dynamic scattering law (part I), 1 a random jump model was adopted for the description of water diffusion to extract a microscopic diffusion coefficient an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 49 publications
4
32
0
Order By: Relevance
“…Undoubtedly, the shell hydration, that causes the swelling of the PVA structure [12,27,43], also contributes to the actual MBs' shell thickness as well as to the rheology and acoustics of aged PVA MBs. It has been reported that the water structured among crosslinked PVA chains can exert a significant influence on the stiffness and the stability of the polymer matrix [54][55][56]. The way in which the long-term modifications in the structural and mechanical properties of the PVA MBs disclosed here reflect a different dynamic of the water confined on the shell surface is an aspect that remains unclarified.…”
Section: Afm Analysismentioning
confidence: 69%
“…Undoubtedly, the shell hydration, that causes the swelling of the PVA structure [12,27,43], also contributes to the actual MBs' shell thickness as well as to the rheology and acoustics of aged PVA MBs. It has been reported that the water structured among crosslinked PVA chains can exert a significant influence on the stiffness and the stability of the polymer matrix [54][55][56]. The way in which the long-term modifications in the structural and mechanical properties of the PVA MBs disclosed here reflect a different dynamic of the water confined on the shell surface is an aspect that remains unclarified.…”
Section: Afm Analysismentioning
confidence: 69%
“…From this result, it shows that when the temperature is increased, the hexanal release from the PVA-β cyclodextrin composite is induced when there is a low relative humidity in the environment. The water molecules got destructured when there is a high temperature (Chiessi et al, 2005), and there are changes in the polymer conformation. This confirms our data that at a high temperature of 33°C, water molecules get destructured rapidly, and due to the polymer chain conformation, hexanal is released quickly at low relative humidity level.…”
Section: Figure 6 the Energy Trajectory Of The Pva-β Cyclodextrin-hementioning
confidence: 99%
“…This property is crucial for the formulation of multicomponent material such as that used in contact lens. Three patents [4,40,41] dealing with the utility of this parameter on the design of contact lens materials are given as examples. Moreover, from the semi IPN structure obtained from polymerized MMA-monomer and PMMA-polymer, Vuorinen et al [42] stated that the formation of a IPN bond is linked to the difference between the solubility parameter of the polymer and the monomer.…”
Section: Solubility Parametermentioning
confidence: 99%
“…Among them, force field transferability, size models, and sampling are among the most important factors. United [4][5][6][7] or All [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] atoms force fields were extensively used during the last 20 years to study phase behavior [8,9], structures [10][11][12], PVA models has been shown by Noorjahan and Choi in 2013 [22]. They observed a drop from 6, 3, and 2.5 MPa respectively for atactic, isotactic, and syndiotactic PVA when the degree of polymerization was increased from 50 to 400 monomer units.…”
Section: Introductionmentioning
confidence: 99%